Quantitative and Qualitative Analysis of Protein Content in Moringa Leaves (Moringa oleifera L.) - Dwi Retnaningtyas Utami; Andi Rahmad Rahim; Sutrisno Adi Prayitno (OJS Universitas Muhammadiyah Gresik, 2022)
Protein is one of the macronutrients that have an important role in the formation of biomolecules. Protein can be found in various plants, one of which is Moringa leaves. Moringa leaves (Moringa oleifera L.) are proven to be effective in treating various diseases, including diabetes, hepatitis, heart disease, and high cholesterol. The purpose of this study was to see if there was protein content in Moringa leaves (Moringa oleifera L.) and how much protein content in Moringa leaves. The parameters used are qualitative tests and quantitative tests, qualitative tests are carried out using the biuret method to determine the presence or absence of protein content in Moringa leaves, while quantitative tests are carried out using spectrophotometric methods to determine protein levels contained in Moringa leaves. From the research results, it is known that Moringa (Moringa oleifera L.) leaves contain protein with a protein content of 2,783; 2,657; 2,547 mg/50g.